2014
DOI: 10.7860/jcdr/2014/9940.4861
|View full text |Cite
|
Sign up to set email alerts
|

Dentition Status, Treatment Needs and Risk Predictors for Dental Caries among Institutionalised Disabled Individuals in Central India

Abstract: The findings of the present study showed that overall caries experience was low but the treatment need was high among these institutionalized disabled individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…[20] Another study conducted by Chand et al . [21] in 2014 in Indore, Madhya Pradesh, had found mean DMFT/deft of 0.97/0.46 in visually impaired children. This was in accordance with the results reported in our study.…”
Section: Discussionmentioning
confidence: 99%
“…[20] Another study conducted by Chand et al . [21] in 2014 in Indore, Madhya Pradesh, had found mean DMFT/deft of 0.97/0.46 in visually impaired children. This was in accordance with the results reported in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Whilst the results of studies varied, research from low‐ and middle income countries generally reported that children with cerebral palsy experience increased risk for dental caries and untreated dental caries 12–15 . However, other findings in low‐ and middle income countries report lower or no difference in caries experience in children with cerebral palsy versus control groups 16–18 …”
Section: Resultsmentioning
confidence: 99%
“…Approximately 35% of studies included adults with cerebral palsy. This group had the highest incidence of dental caries, and increased dental demands relating to dental caries, in both high and low‐middle income countries 17,19–21 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, only a very few studies have been conducted to determine the oral health status and dental caries prevalence of physically challenged children in India. [ 6 7 ]…”
Section: Introductionmentioning
confidence: 99%